Qatar's Magical Land: An Ecocriticism Study on the Representation of Nature in Dreamers Music Video by FIFA World Cup - Emy Trisna Juwita; Adhisty Maheza Fitri; Annisa Maulidina Haqi; Rina Saraswati (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
Abstract Qatar, as the host of the World Cup 2022, has released a music video to enliven the euphoria. The music video is believed to indirectly present several issues including environmental issues. This research aims to examine the depiction of nature in the Dreamers music video by Jungkook and Fahad Al Kubaisi for the official soundtrack of FIFA World Cup 2022. This paper uses ecocriticism interest which takes an earth-centered approach to a literary study by looking at the role nature plays in a given work proposed by Cheryll Glotfelty. The result of the study shows that the music video contains some nature representations which are the existence of pearls as Qatar's main income source before oil discovery, the whale shark as the country's representation to signified its new image, and the white snowy tree emphasizing a climate change that has been a serious concern in the Arab world. Keywords: Ecocriticism, Music Video, Qatar, Representation, World Cup 2022